Treatment of asthma in preschool children with slow release theophylline. Issue 8 (August 1985) - Loftus, B G; Price, J F
Abstract : Fifty two preschool children with asthma were given a recommended regimen of slow release theophylline. There was wide variation in the metabolism of theophylline. The approach adopted gave disappointing results. Nine children did not comply, and 16 stopped treatment because of side effects. Of the remainder, control of asthma was poor in 15 and satisfactory in 12.